2014
DOI: 10.2174/0929867321666140716092052
|View full text |Cite
|
Sign up to set email alerts
|

A Glimpse of Matrix Metalloproteinases in Diabetic Nephropathy

Abstract: Matrix metalloproteinases (MMPs) are proteolytic enzymes belonging to the family of zinc-dependent endopeptidases that are capable of degrading almost all the proteinaceous components of the extracellular matrix (ECM). It is known that MMPs play a role in a number of renal diseases, such as, various forms of glomerulonephritis and tubular diseases, including some of the inherited kidney diseases. In this regard, ECM accumulation is considered to be a hallmark morphologic finding of diabetic nephropathy, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 232 publications
(220 reference statements)
2
47
0
5
Order By: Relevance
“…15,19 However, some reports indicate biphasic modulation of MMP-9, with initial activation followed by a decline in later stages of DN. 20 In another study, similar biphasic response is reported for activity of superoxide dismutase and catalase in pathogenesis of acute kidney injury induced by cisplatin and also hyperlipidimia induced by high fructose diet. 21 The role of MMP-9 in the secretion of growth factors and cytokines has also been reported.…”
Section: Introductionsupporting
confidence: 58%
“…15,19 However, some reports indicate biphasic modulation of MMP-9, with initial activation followed by a decline in later stages of DN. 20 In another study, similar biphasic response is reported for activity of superoxide dismutase and catalase in pathogenesis of acute kidney injury induced by cisplatin and also hyperlipidimia induced by high fructose diet. 21 The role of MMP-9 in the secretion of growth factors and cytokines has also been reported.…”
Section: Introductionsupporting
confidence: 58%
“…The relevant mechanism(s) or the molecules involved in increased ECM expression and their regulation in kidney in diabetic state has been extensively investigated. To name a few are glucose transporter proteins (GLUTs) [11], protein kinase C (PKC) [12], advanced glycation end-products (AGEs) [13], reactive oxygen species (ROS) [14], Matrix metallo-proteinases (MMPs) [15, 16], microRNA [17], growth factors/cytokines and hormones [18, 19]. The latter two would include transforming growth factor β (TGF-β), platelet-derived growth factor (PDGF), growth hormone-insulin-like growth factor (GH-IGF), connective tissue growth factor (CTGF) and Angiotensin II (Ang II) etc.…”
Section: Extracellular Matrix Proteinsmentioning
confidence: 99%
“…MMPs are a family of zinc-dependent proteolytic enzymes that degrade various components of ECM and mediate ECM remodeling in vertebrates [3]. MMPs are proteolytic enzymes belonging to the family of zinc-dependent endopeptidases that are capable of degrading almost all the proteinaceous components of the ECM [4]. MMPs, collectively called matrixins, regulate also the biological activity of nonmatrix substrates such as cytokines, chemokines, receptors, growth factors and cell adhesion molecules [5].…”
mentioning
confidence: 99%